Analysis of Financial Performance Tobacco Listed in Indonesia Stock Exchange - Fadlan Rusdana; Endri Endri (Universitas Medan Area, 2020)
This study aims to determine and analyze the financial performance of sub-sector tobacco industry listed on Indonesia Stock Exchange (IDX). The objects taken in this study were 4 tobacco industry companies listed on the Indonesia Stock Exchange during the 2014-2018 period. The method used in this research is descriptive quantitative, the results of financial ratio analysis using liquidity ratios, solvency ratios, profitability ratios. The results of the calculation of the liquidity ratio showed that PT HM Sampoerna, PT Gudang Garam was the best performing company, the solvency ratio calculation showed PT. HM Sampoerna and PT Wismilak have a debt ratio below the industry average, while according to the profitability ratio PT HM Sampoerna and PT Gudang Garam get a percentage of profits above the industry average. From the calculation of the 3 ratios, PT. HM Sampoerna and PT. Gudang Garam are two companies that are quite dominant in terms of business volume, the performance of the two companies is also very good, it can be valued from its net income which always experiences an upward trend every year but this positive trend does not always mean both in terms of asset utilization and company equity.